THE FACTORS INFLUENCING STUDENTS’ ENGLISH LISTENING COMPREHENSION - Arifin, Amrul; Supardi, Iwan; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research is aimed to investigate the factors influencing students? English listening comprehension on the eleventh grade students of SMAN 10 Pontianak in academic year 2014/2015.The writer applied a case study in this research. The samples of this research are 60 students (26 females and 34 males) out of 217 students as population, taken randomly from 6 classes (3 sciene classes and 3 social classes). The data was collected by using questionnaire, and analyzed by using SPSS. The result of this research showed that the main factor influencing students? English listening comprehension was vocabulary. The lack of vocabulary caused other problems, such as hard to follow the speed of speaker, not ready to listen the conversation, vocabulary that speaker used was hard, hard to differentiate the homophone words, not interested to listen to English conversation, hard to get the information from the speaker, the topic of conversation felt hard and dislike of the topic of conversation. Keywords: Listening Comprehension, Case Study Abstrak: Penelitian ini bertujuan untuk mengetahui factor ? factor yang mempengaruhi pemahaman mendengar Bahasa Inggris Siswa kelas 11 SMAN 10 Pontianak pada tahun akademik 2014/2015. Peneliti menerapkan jenis penelitian studi kasus. Sampel penelitian ini 60 siswa (26 laki ? laki ? dan 34 perempuan) dahri total populasi 217 siswa, yang diambil secara acak dari 6 kelas (3 kelas IA dan 3 Kelas IS). Data diperoleh melalui kuesioner dan dianalisis menggunakan SPSS.  Hasilnya menunjukkan bahwa factor utama yang mempengaruhi kemampuan mendengar Bahasa Inggris siswa adalah kosakata. Kurangnya kosakata mengakibatkan masalah lainnya seperti, kesulitan mengikuti kecepatan pembicara, ketidaksiapan mendengar percakapan, kosakata sulit yang digunakan pembicara, kesulitan membedakan kata yang bersifat homofon, ketidaktertarikan mendengar dalam Bahasa Inggris, kesulitan memperoleh informasi dari pembicara, topic pembicaraan terasa berat dan ketidaktertarikan terhadap topic pembicaraan. Kata Kunci: Pemahaman Mendengar, Studi Kasus